Synthesis, characterization and ethanol sensing properties of peripheral and non-peripheral tetrakis-(3,6-dihexyl-7-oxy-4-methylcoumarin)substituted zinc(II), cobalt(II), and copper(II) phthalocyanines - (:unkn) unknown (ELSEVIER SCI LTD, 2019)
Phthalocyanines bearing coumarin moiety may exhibit interesting properties and also can soluble in organic solvents, easily. In this work, the phthalocyanine compounds bearing tetra-(3,6-dihexyl-7-oxy-4-methylcoumarin) units were synthesized and characterized. Firstly, the starting coumarin compound was synthesized by Pechmann condensation and then phthalonitrile compounds were synthesized by nucleofilic aromatic substitution. Phthalocyanine compounds were synthesized by cyclotetramerization of phthalonitriles. These compounds were characterized by spectroscopic methods such as FT-IR, H-1 NMR, C-13 NMR, electronic absorption spectra, MALDI-TOF mass and elemental analyses as well. The effect of the structure (position of substitution, central metal atom, etc.) of phthalocyanines on electronic absorption spectra and aggregation behavior was also investigated in this paper. In another set of experiments, the effects of the position of methylcoumarin substituent on ethanol vapor sensing performance of the synthesized compounds were investigated and discussed. The observed sensitivities of peripheral and non-peripheral substituted phthalcyanine films are different in spite of their similar bond numbers, indicating significant role of position of the substituent in interaction mechanism. According to the results, the peripheral substituted Pc based sensor not only had high sensitivity towards ethanol vapor, but exhibited very short response time and recovery times. When the concentration of ethanol reached 250 ppm, sensitivity and the response time of peripheral substituted CoPc reached 1.1 x 10(-2) ppm(-1) which was two-fold that than of non-peripheral substitueted CoPc. While peripheral substituted CoPc based sensor shows a response time of 70 s towards 250 ppm concentration of ethanol vapor, the response time of the non-peripheral substitueted CoPc based sensor was about 270 s. As a result, the presented peripheral methyl coumarin substituted compounds are good candidates for ethanol sensing applications.
Keywords: Coumarin; Phthalocyanine; Aggregation; Ethanol sensing; Faster response; SUBSTITUTED ZINC(II); ORGANIC VAPORS; THIN-FILMS; GAS SENSOR; METAL-FREE; BEARING; BEHAVIOR; ADSORPTION; NANOWIRES; ACID